2018
DOI: 10.1111/imj.13735
|View full text |Cite
|
Sign up to set email alerts
|

Diabetic ketoacidosis in adult patients: an audit of factors influencing time to normalisation of metabolic parameters

Abstract: Lower admission pH levels and higher admission serum potassium levels are independent predictors of slower time to resolution of DKA. This may assist to stratify patients with DKA using markers of severity to determine who may benefit from closer monitoring and to predict LOS.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
26
2
13

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(45 citation statements)
references
References 25 publications
4
26
2
13
Order By: Relevance
“…13 It is interesting to note that this analysis reports a substantially lower incidence of infection compared to previous studies including from this facility, despite the tropical climate. [3][4][5][6] However, the infection incidence of 14.5% was similar to that reported by Randall et al 14 , who reviewed low socioeconomic status minority patients. That study reported the major precipitant of DKA to be noncompliance with insulin at 68%, similar to our own findings.…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…13 It is interesting to note that this analysis reports a substantially lower incidence of infection compared to previous studies including from this facility, despite the tropical climate. [3][4][5][6] However, the infection incidence of 14.5% was similar to that reported by Randall et al 14 , who reviewed low socioeconomic status minority patients. That study reported the major precipitant of DKA to be noncompliance with insulin at 68%, similar to our own findings.…”
Section: Discussionsupporting
confidence: 86%
“…1,2 International data demonstrate that infection is one of the most common precipitating causes of DKA. 3,4 Lee et al 5 recently demonstrated that 29% of DKA presentations at a large tertiary Australian hospital were associated with the presence of infection. Our facility previously showed that 29-36% of DKA presentations had been precipitated by infection.…”
Section: Introductionmentioning
confidence: 99%
“…The most common precipitants of DKA in type 1 diabetes mellitus (T1DM) are insulin omission (42%) and infection (30%) . Other important precipitants include medications (glucocorticoids, antipsychotics, SGLT2i and immune CPI), myocardial ischaemia, eating disorders and unrecognised malfunction of continuous subcutaneous insulin infusion devices.…”
Section: Methodsmentioning
confidence: 99%
“…To meet this goal, scientific societies worldwide have developed recommendations and step -by -step algorithms for DKA therapy. 20,21 They are clear, easy to follow, and evidence based. Literature data confirm the benefits of using appropriate algorithms in DKA treatment.…”
Section: Patients and Methods Study Populationmentioning
confidence: 99%